Tanjungpura University students' perceptions against new design of BPJPH halal logo using smartPLS 4.0 - Budiman, Riadi (Akademisi dan Saintis Indonesia (ASASI), 2024)
Changes to the halal logo's design occurred as a whole, both in terms of shape and colour, which are thought to refer to one culture. The new logo design is thought to prioritise creative writing in Arabic over halal writing. The Ministry of Religion, on the other hand, has explained a new design concept that is distinct and has a strong personality that embodies Indonesian values. According to the government, the modification to the Indonesian halal logo also signalled the transfer of authority to give halal certification from the Indonesian Ulema Council to the Halal Product Guarantee Organizing Agency (BPJPH. This study aims to identify Tanjungpura University students' perceptions of modifications to the new Halal logo design and to analyze student perceptions of adjustments to the new Halal logo using the mixing technique. The logo has six factors: original, legitimate, simple, memorable, easily connected with the organization, and easily adaptable for all visuals. Based on test results assisted by smartPLS 4.0, it shows a p-value ≤ 0.05. This signifies that the relationship between the variables is substantial, and the hypothesis derived from the relationship between the two variables is accepted. Meanwhile, the findings of qualitative testing employing interview methodologies revealed that 70% of respondents were intrigued by the logo. Research-based on interest variables reveals that 65% of respondents have halal awareness as a factor that emerges from within themselves. Examining these two components proves and validates the hypothesis results from quantitative testing.